Post-Communist Transitional Justice: Lessons from Twenty-Five Years of Experience - Stan, Lavinia; Nedelsky, Nadya (Cambridge University Press, 2015)
Taking stock of the twenty-fifth anniversary of the collapse of the communist regimes of Central and Eastern Europe, this volume explores the ways these societies have grappled with the serious human rights violations of past regimes. It focuses on the most important factors that have shaped the nature, speed, and sequence of transitional justice programs in the period spanning the tumultuous revolutions that brought about the collapse of the communist dictatorships and the consolidation of new democratic regimes. Contributors explain why leaders made certain choices, discuss the challenges they faced, and explore the role of under-studied actors and grassroots strategies. Written by recognized experts with an unparalleled grasp of the region's communist and post-communist reality, this volume addresses far-reaching reckoning, redress, and retribution policy choices. It is an engaging and carefully crafted volume, and it covers a wide variety of cases and discusses key transitional justice theories using both qualitative and quantitative research methods.
Keywords: References - Boel et al. (2021), Archives and Human Rights

The History of the Stasi: East Germany's Secret Police, 1945-1990 - Gieseke, Jens (Berghahn Books, 2015)
A well-balanced and detailed look at the East German Ministry for State Security, the secret police force more commonly known as the Stasi. “This is an excellent book, full of careful, balanced judgements and a wealth of concisely-communicated knowledge. It is also well written. Indeed, it is the best book yet published on the MfS.”―German History The Stasi stood for Stalinist oppression and all-encompassing surveillance. The “shield and sword of the party,” it secured the rule of the Communist Party for more than forty years, and by the 1980s it had become the largest secret-police apparatus in the world, per capita. Jens Gieseke tells the story of the Stasi, a feared secret-police force and a highly professional intelligence service. He inquires into the mechanisms of dictatorship and the day-to-day effects of surveillance and suspicion. Masterful and thorough at once, he takes the reader through this dark chapter of German postwar history, supplying key information on perpetrators, informers, and victims. In an assessment of post-communist memory politics, he critically discusses the consequences of opening the files and the outcomes of the Stasi debate in reunified Germany. A major guide for research on communist secret-police forces, this book is considered the standard reference work on the Stasi.
Keywords: References - Boel et al. (2021), Archives and Human Rights

Transitional Justice after German Reunification: Exposing Unofficial Collaborators - Espindola, Juan (Cambridge University Press, 2015)
How do societies transitioning from oppressive to democratic rule hold accountable those citizens who contributed to maintaining injustice in the ancient regime by secretly denouncing fellow citizens? Is their public identification a way of fulfilling respect for those who suffered harm as a result of their collaboration? And is public identification respectful of denunciators themselves? This book pursues these questions through a multidisciplinary investigation focusing on the denunciators for the East German secret police and the Ministry of State Security and the way in which they have been publicly unveiled in contemporary German society. The book evaluates the justifications that social actors offer to support or oppose public identifications; how targeted collaborators react to this social practice; and whether it achieves its intended purpose. At every stage, the book asks whether the motivations and the consequences of public identifications honor or undermine the value of respect for people.
Keywords: References - Boel et al. (2021), Archives and Human Rights

News from the ICA Human Rights Working Group - 2015-09 (September) - Peterson, Trudy Huskamp (ICA, 2015)
Keywords: Sep'15 Newsletter has Oct'15 Newsletter in it. No Sep'15 newsletter